Do Stringent Environmental Policies Deter FDI? M&A versus Greenfield - Sylwia Bialek; Alfons J. Weichenrieder (Environmental and Resource Economics, 2021)
Strict environmental regulation may deter foreign direct investment (FDI). The paper develops the hypothesis that regulation predominantly discourages FDI that is conducted as Greenfield investment rather than mergers and acquisitions (M&A). The hypothesis is tested with German firm-level FDI data. Empirically, stricter regulation reduces new Greenfield projects in polluting industries, but indeed has a much smaller impact on the number of M&As. This significant difference is compatible with the fact that existing operations often benefit from grandfathering rules, which provide softer regulation for pre-exisiting plants, and with the expectation that for M&As part of the regulation is capitalized in the purchase price. The heterogeneous effects help explaining mixed results in previous studies that have neglected the mode of entry.
Keywords: F23; F64; Q50; Q58; 330; Environmental stringency; Entry mode; Pollution haven hypothesis; Foreign direct investment